Photocatalytic activity of La-doped ZnO nanostructure materials synthesized by sonochemical method - Anukorn Phuruangrat (2018)
© 2015, The Nonferrous Metals Society of China and Springer-Verlag Berlin Heidelberg. ZnO nanostructure materials doped with different La contents were synthesized by sonochemical method. The products were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Raman spectroscopy, and Fourier transform infrared spectroscopy (FTIR). In this research, XRD patterns of pure ZnO and La-doped ZnO are specified as hexagonal wurtzite ZnO structure with no detection of La2O3 phase. SEM and TEM characterization revealed the flower shape of pure ZnO built-up from petals of hexagonal prisms with hexagonal pyramid tips. Upon doping with La, the flower-shaped ZnO is broken into individual 1D prism-like nanorods. Photocatalytic activities of the as-synthesized products were determined by measuring the degradation of methylene blue (MB) under ultraviolet–visible (UV) light irradiation. Among them, the 2.0 mol% La-doped ZnO shows better photocatalytic properties than any other products.